Supply chain management in the internet age - Lee, Hau (Stanford executive briefings, 2001)
"Taped live May 23, 2001 at Stanford University." Great innovations take place in 3 stages: substitution effect, scale effect, and the structural effect. Companies can't be satisfied with these effects when enjoying the benefits of the Internet on supply chain management. Companies need to identify the opportunity for structural changes to their supply chain, and enable these changes to take place. The result will be new collaborative ventures, even entirely new product lines. Lee shows how select companies have leaped ahead by encouraging the structural changes precipitated by the growth of the Internet.